Establishment of a Novel Porcine Model to Study the Impact of Active Stretching on a Local Carrageenan-Induced Inflammation. (November 2020) - Vergara, Dennis Muñoz; Berrueta, Lisbeth; Carmody, Colleen; An, Xingxing; Wayne, Peter M.; Zavacki, Ann Marie; Langevin, Helene M.
Abstract : Objective: Active stretching of the body is integral to complementary mind-body therapies such as yoga, as well as physical therapy, yet the biologic mechanisms underlying its therapeutic effects remain largely unknown. A previous study showed the impact of active stretching on inflammatory processes in rats. The present study tested the feasibility of using a porcine model, with a closer resemblance to human anatomy, to study the effects of active stretching in the resolution of localized inflammation. Design: A total of 12 pigs were trained to stretch before subcutaneous bilateral Carrageenan injection in the back at the L3 vertebrae, 2 cm from the midline. Animals were randomized to no-stretch or stretch, twice a day for 5 mins over 48 hrs. Animals were euthanized for tissue collection 48 hrs postinjection. Results: The procedure was well tolerated by the pigs. On average, lesion area was significantly smaller by 36% in the stretch group compared with the no-stretch group ( P = 0.03). Conclusion: This porcine model shows promise for studying the impact of active stretching on inflammation-resolution mechanisms. These results are relevant to understanding the stretching-related therapeutic mechanisms of mind-body therapies. Future studies with larger samples are warranted. Abstract : Supplemental digital content is available in the text.